MODERNIZATION OF VANES AND BLADES OF GAS TURBINES WITH HONEYCOMB SEAL - V. T. Buglaev; S. V. Perevezentzev; D. V. Danilenko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper shows the ways how to modernize vanes and blades of gas turbines with honeycomb seals in a guide vane and an impeller. Recommendations on the optimization of radial slots and improvement of factors relevant to cellular structure of a honeycomb seal have been elaborated.